1997
DOI: 10.1128/aem.63.3.1185-1188.1997
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fecal bacteria with bile acid 7 alpha-dehydroxylating activity for the presence of bai-like genes

Abstract: Eubacterium sp. strain VPI 12708 has several bile acid-inducible (bai) genes which encode enzymes in the bile acid 7␣-dehydroxylation (7␣DeOH) pathway. Twelve 7␣DeOH-positive intestinal bacterial strains were assayed for 7␣DeOH activity, and 13 strains were tested for hybridization with bai genes. Cholic acid 7␣DeOH activity varied greatly (>100-fold) among these strains. Southern blot experiments showed that DNA prepared from 7 of 13 strains hybridized with at least one of the bai genes from Eubacterium sp. s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 22 publications
(10 reference statements)
2
59
0
Order By: Relevance
“…1C). The bile acid concentration chosen reflects both in vivo physiologically relevant concentrations of bile acids in fecal water (18,19) and concentrations used previously in numerous in vitro studies of C. scindens strains (6,10,15). Separate additions of CA in early and mid-log phase have been previously shown to result in robust induction of the bai regulon (7).…”
Section: Resultsmentioning
confidence: 99%
“…1C). The bile acid concentration chosen reflects both in vivo physiologically relevant concentrations of bile acids in fecal water (18,19) and concentrations used previously in numerous in vitro studies of C. scindens strains (6,10,15). Separate additions of CA in early and mid-log phase have been previously shown to result in robust induction of the bai regulon (7).…”
Section: Resultsmentioning
confidence: 99%
“…Additional changes to the gut microbiome in response to the introduction of solid foods in year two of life include the appearance of Clostridium hiranonis, C. hylemonae, C. leptum, C. scindens, and C. sordellii. These organisms along with eubacterium and bacteroides transform primary bile acids into secondary bile acids for the first time since birth (Figure 2) (Hylemon and Stellwag, 1976;Doerner et al, 1997;Kitahara et al, 2001). They possess dehydroxylases capable of removing hydroxyl groups from the a3, 7 and 12 carbon position in primary bile acids.…”
Section: The Role Of Clostridium Species In the Transformation Of Primentioning
confidence: 99%
“…Since the hydroxyl groups at the 7 carbon position is most susceptible to dehydroxylation, it is removed most often. Dehydroxylases responsible for removal of the 7 carbon hydroxyl group are regulated by a series of bile acid inducible gene operons (Doerner et al, 1997;Ridlon et al, 2016). Dehydroxylation increases the hydrophobicity of the bile which, in turn, increases membrane binding, and toxic and metabolic effects (Ridlon et al, 2006).…”
Section: The Role Of Clostridium Species In the Transformation Of Primentioning
confidence: 99%
“…Early molecular studies showed that C. scindens and Eg. lenta, which both belong to the functional group of biliary steroid-metabolising bacteria, are common members of the human intestinal microbiota (Bokkenheuser et al, 1979;Doerner et al, 1997;Schwiertz et al, 2000;Kitahara et al, 2001). Besides, as in the case of SECO demethylation by P. productus, the dehydroxylation activity was observed for several strains of Eg.…”
Section: Identification Of Seco-dehydroxylating Bacteriamentioning
confidence: 99%